2005
DOI: 10.1261/rna.2130705
|View full text |Cite
|
Sign up to set email alerts
|

A surprisingly large RNase P RNA in Candida glabrata

Abstract: We have found an extremely large ribonuclease P (RNase P) RNA (RPR1) in the human pathogen Candida glabrata and verified that this molecule is expressed and present in the active enzyme complex of this hemiascomycete yeast. A structural alignment of the C. glabrata sequence with 36 other hemiascomycete RNase P RNAs (abbreviated as P RNAs) allows us to characterize the types of insertions. In addition, 15 P RNA sequences were newly characterized by searching in the recently sequenced genomes Candida albicans, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
(46 reference statements)
4
23
0
Order By: Relevance
“…41 RNase P. Ascomycete mitochondrial RNase P RNAs are, on the other hand, highly reduced in size and lack most of the sequence and structural elements conserved in other RNase P RNAs. [42][43][44][45] The human (and presumably other metazoans) mitochondrial RNase P lacks the RNA subunit entirely; the RNase P catalytic function has been replaced by a Rube Goldberg triad of unrelated proteins. 46,47 The secondary structure of RNase P RNAs from primitive plastids are similar to those of cyanobacteria, from which they derive.…”
Section: Eukaryotic Rnase P Rnasmentioning
confidence: 99%
“…41 RNase P. Ascomycete mitochondrial RNase P RNAs are, on the other hand, highly reduced in size and lack most of the sequence and structural elements conserved in other RNase P RNAs. [42][43][44][45] The human (and presumably other metazoans) mitochondrial RNase P lacks the RNA subunit entirely; the RNase P catalytic function has been replaced by a Rube Goldberg triad of unrelated proteins. 46,47 The secondary structure of RNase P RNAs from primitive plastids are similar to those of cyanobacteria, from which they derive.…”
Section: Eukaryotic Rnase P Rnasmentioning
confidence: 99%
“…Helix numbering follows their putative homology with bacterial structures (Haas et al 1994). The PRNA structure model is derived from (Kachouri et al 2005), while the insertions are shown with arrows.…”
Section: Catalytic Domain Of Mrp Rnamentioning
confidence: 99%
“…The eP8 and eP9 helicesa re ubiquitous components of eukaryotic PRNAs (Frank et al2000;Kachouri et al 2005;Marquez et al 2005;Piccinellie ta l. 2005). Basedo n sequence analysis, an equivalent helix in the MRP RNAi s the helix that preservesasignificant number of nucleotides fromits counterpartinthe PRNA.This criterion led to the identificationofthe helices P8 and P9 in the MRP RNA of Encephalitozoon cuniculi (Fig.3 A), where the P8 in the MRP RNA is 100% identical to the P8 in the PR NA, and theP9s have four nucleotidesconserved in theterminalloop (Fig.3A).…”
Section: The Specificity Domain Of Mrp Rnamentioning
confidence: 99%
See 2 more Smart Citations